Common problems Encountered during Lactation and their Management in a Lactation Management Center - Shimul, Sabiha; Chowdhury, Sameena; Jabeen, Mahe; Salma, Ummay; Akter, Mahbuba; Sarkar, Anita (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Breastfeeding is widely known to be beneficial for infants and the mothersand also economically advantageous for the community. Objective: The principal purpose of this study was to explore the common problemsencountered during lactation and their management in a lactation management center. Method: A cross sectional study was conducted at lactation management center of Instituteof Child and Maternal Health (ICMH), Dhaka. A total of 100 lactating mothers were recruitedconsecutively during the period of August 2008 to October 2008. Data was collected byhistory taking and required examination. Result: In this study, 46.0% mothers complained of poor milk secretion, 13.0% had breastengorgement, 9.0% had cracked nipple, 3.0% had inverted nipple, 2.0% had nipple infection,2.0% had flat nipple, 1.0% had sore nipple, 1.0% had breast abscess and in 23% casesthere was no reasonable cause. During interview twenty seven percent of the mothers wereadvised to start nursing as soon as possible; 45.0% mothers breast fed on demand, 75.0%mothers demonstrated proper breast feeding technique, 36.0% mothers avoided use ofartificial milk, 10.0% mothers applied last part of milk on nipple, then dry by exposing to air,12.0% mothers manually express milk from the areola before breast feed if it is engorgedand 1.0% advised to slip the index or little finger into the infant’s mouth between his/hergums before the infant is taken off of the breast, to break suction. Conclusion: Almost half of the mothers complained of less milk production. Apart from this13.0% mothers had breast engorgement, 9.0% mothers had cracked nipple and no reasonablecause for lactation problem was found in 23.0% cases. More than half of the mothers hadincorrect knowledge and skill of breast feeding. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 36-39